"Legumix" Stylosanthes pellets: A healthier and more sustainable animal feed. (September 2019) - Sylvester-Bradley, Rosemary
The development of a range of animal feeds based on leaf meal of the tropical forage legume Stylosanthes guianensis var. guianensis ("tropical alfalfa") in Costa Rica, their potential for improving health of animals and consumers of animal products, the local and national economy, and ecological implications are described. A subproduct of the oil palm industry (palm oil fatty acid distillate) is used to supplement the Stylosanthes leaf meal with sufficient energy to produce a complete pelleted feed. Customer case studies showed that Stylosanthes -based feeds are highly palatable and improve health and performance of farm animals (horses, rabbits, calves, sheep, and goats) over that observed when using grain-based feeds. The improved quality of Stylosanthes -based over grain-based feed for ruminants could play an important role in the reduction of methane emissions and their negative consequences for climate change. A sustainable system whereby Stylosanthes is planted in association with plantation trees is proposed, providing a supplementary income for tree farmers and other benefits, such as weed control and soil amelioration. Stylosanthes can be rotated with sugarcane and pineapple, and cash flow projections show that Stylosanthes leaf meal production would be a favorable alternative activity for local farmers, yielding a greater and more constant income than sugarcane. Achieving economy of scale in the industrial process would permit production at lower cost to compete with the price of imported grain-based feed. Lack of finance is currently the major obstacle to scaling up the process, implementing the technology in different countries, and obtaining the concomitant benefits of food security, import substitution, improved ecological sustainability, and healthiness of animal products.